2018
DOI: 10.1111/epi.14568
|View full text |Cite
|
Sign up to set email alerts
|

Variants p.Q1236H and p.E1143G in mitochondrial DNA polymerase gamma POLG1 are not associated with increased risk for valproate‐induced hepatotoxicity or pancreatic toxicity: A retrospective cohort study of patients with epilepsy

Abstract: Summary Objective Previous studies have suggested that heterozygous variants p.Q1236H and p.E1143G in mitochondrial DNA polymerase gamma (POLG1) increase the risk for liver injury for patients on valproate (VPA) therapy. We assessed the prevalence of these common variants and seven other pathogenic mutations in POLG1 and determined the occurrence of VPA‐induced hepatotoxicity (VHT) or pancreatic toxicity in a cohort of patients with epilepsy. Methods Patients with epilepsy (N = 367) were retrospectively identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…There is an emerging clinical picture of ID, epileptic encephalopathy with speech and language deficits and autism due to a broad range of variants in the IQSEC2 gene, including the missense variants in the PH domain that we report here. When we include the five novel cases presented in this study, there are 29 distinct nonsynonymous missense variants in the IQSEC2 gene reported in 34 unrelated cases and families 2,3,12,14‐20 . Most of these variants occur in known functional domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an emerging clinical picture of ID, epileptic encephalopathy with speech and language deficits and autism due to a broad range of variants in the IQSEC2 gene, including the missense variants in the PH domain that we report here. When we include the five novel cases presented in this study, there are 29 distinct nonsynonymous missense variants in the IQSEC2 gene reported in 34 unrelated cases and families 2,3,12,14‐20 . Most of these variants occur in known functional domains.…”
Section: Discussionmentioning
confidence: 99%
“…When we include the five novel cases presented in this study, there are 29 distinct nonsynonymous missense variants in the IQSEC2 gene reported in 34 unrelated cases and families. 2,3,12,[14][15][16][17][18][19][20] Most of these variants occur in known functional domains. Within the catalytic Sec7 domain, nine missense variants with three recurrent variants across eight separate cases or families, impact a total of 44 affected individuals (39 males and five females).…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that valproate administration increased thiobarbituric acid reagent content and nitric oxide (NO) production in the liver tissue, attributing to increased oxidative/nitrosative stress [ 27 ]. Interestingly, a 2018 cohort study noticed that POLG1 was not solely associated with an increased risk of valproate-induced liver toxicity but required a combination of other pathogenic mutations as well [ 82 ], thereby suggesting that only epileptic patients with the aforementioned pathologies/mutations may be prone to develop liver toxicity post valproate treatment.…”
Section: Broad and Narrow Spectrum Anti-seizure Drugsmentioning
confidence: 99%
“…POLG which codes mitochondrial DNA polymerase γ (polγ) is associated with an increased risk of VPA-induced hepatotoxicity, and even fatal damage to liver cells (Saneto et al, 2010;Stewart et al, 2010;Sitarz et al, 2014) with a >20-fold risk elevation (Stewart et al, 2010). When a large retrospective analysis was performed, no association was demonstrated in the VPA DILI patients (Hynynen et al, 2018), suggesting a genetic variation in the population and prospective RCT studies are still invaluable.…”
Section: Genetic Biomarkers For Vpa-induced Liver Injurymentioning
confidence: 99%